آليات تفعيل النظام الضريبي في القانون الجزائري وتأثيرها على الاقتصاد الوطني - ـ لعوينــــــي, رنــــــدة; مجوري, مسعودة (University of Eloued جامعة الوادي, 2023)
نظ ا ر لمتطك ا رت التي ط أ رت عمى مفيك الضريبة عامة كالضريبة المباشرة، كالتي أصبحت بمقتضاىا فريضة إل ا زمية تحددىا الدكلة كيمتز الممكؿ بأدائيا بلا مقابؿ تمكينا لمدكلة مف القيا بتحقيؽ أىداؼ المجتمع، كلا شؾ أف الضريبة لا تستطيع أف تقك بيذا الدكر اليا المنكط بيا، إلا إذا قامت عمى أساس مف العدؿ، عمى أف يتحمؿ كؿ مكاطف الضريبة عمى قدر مقدرتو التكمفية كتحقيؽ المساكاة في الم ا ركز القانكنية بيف المكاطنيف أما الض ا رئب. كلقد ساى الإصلاح الضريبي في زيادة المردكدية المالية لمختمؼ الض ا رئب، لكنو ما ا زؿ بعيدا عف الطمكحات المعمنة في إطار السياسة الضريبية المنتيجة كالتي محكرىا الأساسي يكمف في إحلاؿ الجباية. لذلؾ يجب عمى المشرع الضريبي تحسيف تنظي كادارة النظا الضريبي كبالتالي تحسينو، ضؼ إلى ذلؾ يجب تحسيف التحصيؿ الضريبي كمكافحة ظاىرة التيرب الضريبي مف خلاؿ نشر الكعي الضريبي قصد تغيير الذىنيات المعادية لمضريبة كالاىتما أكثر بالإدارة الضريبية حتى تؤدم مياميا عمى الكجو الكامؿ. In view of the developments that have taken place in the concept of general tax and direct tax, according to which it has become a mandatory obligation determined by the state, and the taxpayer is obliged to perform it free of charge to enable the state to achieve the goals of society. There is no doubt that the tax cannot play this important role assigned to it, unless it is based on It is fair, provided that every citizen bears the tax according to his ability to afford it, and the equality of legal positions between citizens in front of taxes is achieved. The tax reform has contributed to increasing the financial returns of various taxes, but it is still far from the aspirations declared within the framework of the adopted tax policy, the main focus of which lies in the replacement of collection. Therefore, the tax legislator must improve the organization and management of the tax system and thus improve it. In addition, tax collection must be improved and the phenomenon of tax evasion must be combated by spreading tax awareness in order to change anti-tax mentalities and pay more attention to the tax administration in order to fully perform its tasks.
مذكرة ماستر
Keywords: الضريبة المشرع السياسة الضريبية فعالية النظا الضريبي.; tax - the legislator - tax policy - the effectiveness of the tax system.